2014
DOI: 10.2147/ahmt.s54339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mass media and Internet on sexual behavior of undergraduates in Osogbo metropolis, Southwestern Nigeria

Abstract: IntroductionThe influence of media portrayals of sexual attitudes and normative expectations of young people at a critical developmental stage is of public health concern.ObjectivesTo examine the role of mass media and Internet utilization in shaping the sexual health attitudes and behaviors of young undergraduates in Osogbo metropolis, Osun State, Nigeria.Materials and methodsIn a descriptive cross-sectional study, 400 undergraduates were selected using a multistage random sampling technique. Four hundred and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
46
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 23 publications
14
46
2
Order By: Relevance
“…These ndings are supported by those of previous studies [17,18], signifying that exposure to sex in media messages is a risk factor for early sexual progression. These results are also consistent with ndings of the research conducted in Nigeria [30], indicating that those who used the Internet or accessed sexually explicit materials being more likely to be sexually active as compared to non-exposed counterparts. The study showed that adolescents who ever engaged in sexual intercourse were also more likely to have used alcohol.…”
Section: Discussionsupporting
confidence: 90%
“…These ndings are supported by those of previous studies [17,18], signifying that exposure to sex in media messages is a risk factor for early sexual progression. These results are also consistent with ndings of the research conducted in Nigeria [30], indicating that those who used the Internet or accessed sexually explicit materials being more likely to be sexually active as compared to non-exposed counterparts. The study showed that adolescents who ever engaged in sexual intercourse were also more likely to have used alcohol.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies also support this findings that watching pornography/adult sexual content can negatively influence young men, which motivates them to get involved in premarital sexual relationships and shapes their ideas of sex, sexuality and relationships. 36 37 Respondents agreed that marriage guarantees regular sex and a sexual partner. With marriage, sexual desire can be fulfilled without any additional costs or hassles.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, females are more predisposed to contracting HIV because of early marriage, polygamous relationships and pelvic inflammatory disease which predisposes to microulceration of the genital tract thus increasing the risk of HIV infection [28][29][30]. Sexual intercourse during menstruation and presence of genital ulcers and the use of oral contraceptive, which could induce cervical ectopia due to replacement of squamous by columnar epithelium, also increases the risk of HIV infection for women 5-fold [8].…”
Section: Demographics Of Study Populationmentioning
confidence: 99%